Advancements in Alzheimer’s Disease Therapy: The Role of Anti-Amyloid Monoclonal Antibodies - A Literature Review - Skoczeń, Agnieszka; Rutecka, Natalia; Kaczmarek, Błażej; Kuśnierz-Gibała, Agata; Kruk, Adrian; Kulesza, Michał; Wawrzynów, Weronika; Miłoś, Martyna; Dorosz, Aleksandra; Jakubowska, Magdalena Maria (Journal of Education, Health and Sport, 2025)
Alzheimer’s disease is a neurodegenerative disorder characterized by progressive cognitive decline and neuronal damage. Anti-amyloid monoclonal antibodies such as aducanumab, lecanemab, and donanemab, represent the first disease-modifying therapies for Alzheimer’s disease, specifically targeting amyloid-β plaques, a hallmark of the disease. This review examines the pathogenesis of Alzheimer’s disease, the mechanism of action of these anti-amyloid therapies, and their potential benefits and associated risks, particularly amyloid-related imaging abnormalities (ARIA). While these therapies have demonstrated statistically significant efficacy in reducing amyloid plaques and decelerating cognitive decline, further research is required to confirm their long-term clinical benefits and establish a precise safety profile. Nonetheless, the approval of these monoclonal antibodies constitutes a significant advancement and potentially heralds the beginning of a new era in the treatment of Alzheimer’s disease.